The Compiled Statutes in Force in the District of Columbia Including the Acts of the Second Session of the Congress 1887-89, at 178 (1894) - (:unkn) unknown (My University, 1871)
Act of July 20, 1871: It shall not be lawful for any person or persons to carry or have concealed about their persons any deadly or dangerous. weapons, such as daggers, air-guns, pistols, bowie-knives, dirk- knives, or dirks, razors, razor-blades, sword-canes, slung-shots, or brass or other metal knuckles, within the District of Columbia.
Keywords: CARRY - CONCEALED; CARRY - INTENT TO COMMIT CRIME